The Knowledge and Behavior of Pregnant Women in Nutrition Fulfillment: The Correlational Study - Rizkia, Mira; Ardhia, Dara; Sari, Rini Permata (Babali Publisher, 2023)
Nutrition during pregnancy greatly affects the health status and development of the mother and fetus. Lack of knowledge and behavior of pregnant women about nutrition will increase the risk of mothers experiencing Chronic Energy Deficiency (CED) and anemia. In infants it will increase the risk of Low Birth Weight Babies and premature. The purpose of this study was to determine the correlation between knowledge and behavior of pregnant women in nutrition fulfillment in Aceh Besar. This type of research is quantitative with a cross-sectional study design with 10 villages selected by cluster random sampling with 83 respondents. The data collection tool is a questionnaire that has been tested for content and constructs. Data analysis using chi-square test. The results showed that there was a significant relationship between knowledge and behavior of pregnant women in fulfilling nutrition in Aceh Besar (p: 0.000). Knowledge and behavior of pregnant women in fulfilling good nutrition during pregnancy are expected to prevent maternal and fetal complications also in preventing stunting.